Development of a Stacking Device for Medical Urine Cups - Zhao Peng; Farra A. Jumuddin (Wolters Kluwer Medknow Publications, 2024)
The study focuses on creating a stacking device for medical urine cups, integrating pressing, storing, and collecting mechanisms to streamline palletizing without manual intervention. This approach enhances efficiency and reduces costs. The device features a working table equipped with a pressing device at the top and a holding device below it, followed by a collecting device at the bottom. The pressing device is composed of a motor, a CAM, a pressing cylinder head, an F-shaped frame, and a large spring. This configuration ensures that the urine cups maintain their shape and are tightly stacked without damage. A rubber ring facilitates a snug fit between the shaped column and the urine cup, evenly distributing force. In addition, a small spring and push block separate the column and cup, countering inertia and enhancing stacking quality. The device thus significantly improves the palletizing process of urine cups.